A Criminological Study of Social and Economic Factors in Corruption Crimes - Rhogust, Muhammad; Endah Lestari, Martanti; Bahri, Syaiful; Hermanto (Yayasan Pendidikan Belajar Berdikari, 2022)
This study examines corruption in Indonesia from a criminological perspective, focusing on how social and economic factors contribute to its persistence. Using a qualitative descriptive approach, the research analyzes secondary data from the Corruption Eradication Commission (KPK), Statistics Indonesia (BPS), and Transparency International between 2020 and 2024. The findings reveal that corruption is not merely a legal violation but a socially learned and economically driven behavior embedded in Indonesia’s bureaucratic and cultural structures. Social elements such as patronage, nepotism, and weak moral control intersect with economic pressures like income inequality and inadequate welfare, forming a systemic environment conducive to corruption. Applying Differential Association Theory, Strain Theory, and Rational Choice Theory, this study interprets corruption as both a learned adaptation and a rational response to structural strain. The results highlight the need for multidimensional anti-corruption strategies that integrate institutional reform, socio-economic equality, and cultural transformation. This criminological approach offers deeper insight into the roots of corruption and provides a theoretical foundation for developing more effective preventive policies in Indonesia.